Visual Loss after Scoliosis Surgery: What Do Surgeons and Patients Need to Know? Three Case Reports - Barros, Alderico Girão Campos de; Oliveira, Augusto Ribeiro de Jesus; Cavalvanti, Lucas Rocha; Silva, Luis Eduardo Carelli Teixeira da; Guimarães, João Antonio Matheus (Revista Brasileira de Ortopedia, 2024)
Visual deficit after spinal surgery is rare but tragic. The main causes include external eye injury, cortical blindness, central retinal artery occlusion, and ischemic optic neuropathy. In scoliosis surgery, this complication potentially arises from prolonged surgical time, high blood loss, prone position, hydroelectrolytic imbalance, and cerebrospinal fluid loss.In 849 scoliosis correction surgeries, 3 patients developed postoperative visual deficits: 2 achieved complete visual acuity recovery, but 1 remained with partial sequelae.There are four causes of postoperative amaurosis: ischemic optic neuropathy, central retinal artery occlusion, external eye injury, and cortical blindness. Since the prevention of this complication cannot be assured, it is essential to explain the risk of visual deficits to patients undergoing scoliosis surgery, who must sign the informed consent form.Visual loss after spinal surgery for scoliosis correction is a rare but severe and, sometimes, irreversible complication. The surgical team must know about this possibility in order to adopt preventive measures and reduce its incidence.
Keywords: amaurosis; blindness, cortical; spine/surgery; scoliosis/complications